Monitoring Student Cues: Tracking Student Behaviour in Order to Improve Instruction in Higher Education - McAlpine, L.; Weston, C.; Beauchamp, C.; Wiseman, C.; Beauchamp, J. (Canadian Journal of Higher Education, 2017)
In this paper, we focus on monitoring, a particular aspect of reflection related to teaching. We define monitoring as a feedback mechanism which entails attending to and evaluating a multitude of cues in the envi- ronment in order to evaluate progress towards a goal. We direct our attention to monitoring because it is a way in which a teacher is able to gain understanding of how effective his/her teaching actions are. Thus, knowing what cues to evaluate (and being able to do so) is a critical skill in reflection. Further, we focus exclusively in this paper on the concur- rent monitoring of cues related to students since we believe that attention to student cues while teaching provides teachers with a window into their students’ learning experiences. We call this particular type of reflection, reflection-in-action. As well as depicting multiple examples of monitoring drawn from our research, we explore the contribution of this work to the literature in higher education and to faculty development activities, particularly, to the growing literature on teacher thinking.